(untitled) (Web of Teachers: Inderscience Research, 2025)
In this article we explore the theoretical and practical aspects of English and Uzbek grammar, highlighting the similarities and differences between the two languages. By analyzing their grammatical structures, such as syntax, morphology, and sentence formation, the study aims to provide a comprehensive understanding of how each language functions. Special emphasis is placed on key linguistic features such as verb tenses, word order, noun cases, and gender distinctions. The research also compares the pedagogical approaches to teaching grammar in both languages and offers insights into effective strategies for language acquisition. This cross-linguistic comparison serves as a foundation for future studies on bilingualism and multilingual education.